Impact of economic policy uncertainty and financial constraints on firms' markups: evidence from China. Issue 1 (2nd January 2022) - Du, Xiaofei; Luan, Weixin; Lu, Yuduo
ABSTRACT: Economic policy uncertainty (EPU) hinders global economic recovery and is an important cause of economic recession. Additionally, EPU also hinders the development of firms. In this context, using firms' markups as the breakthrough point, this study analyses how EPU and financial constraints affect firms' markups with the assistance of an econometric model and using an index of EPU and data from Chinese Annual Survey of Industrial Firms. The conclusions are as follows: (1) EPU has a significantly negative impact on firms' markups; (2) both the internal and external financial constraints have a significantly negative impact on firms' markups; (3) the interaction between EPU and internal and external financial constraints has a significantly negative impact on the firms' markups. This study also analyses the differences of firms' heterogeneity. This study is helpful for firms to fully understand the different impacts of internal and external shocks on firms' markups, and provide more targeted reference for policy-making departments, and thus improve the policies' effectiveness.